Patients' perspectives of tuberculosis treatment challenges and barriers to treatment adherence in Ukraine: a qualitative study. Issue 1 (2nd February 2020) - Aibana, Omowunmi; Dauria, Emily; Kiriazova, Tetiana; Makarenko, Olena; Bachmaha, Mariya; Rybak, Natasha; Flanigan, Timothy Palen; Petrenko, Vasyl; Becker, Anne E; Murray, Megan B
Abstract : Objectives: To understand the challenges faced by patients with tuberculosis (TB) and factors that influence TB treatment adherence in Ukraine. Design: Qualitative study. Setting: TB treatment facilities in Kyiv Oblast, Ukraine. Participants: Sixty adults who had undergone treatment for drug-sensitive TB between June 2012 and August 2015. Methods: We conducted semistructured, in-depth, individual interviews among a purposively selected clinical sample of patients previously treated for drug-sensitive TB. Interview content encompassed WHO's framework for barriers to adherence to long-term therapies and included questions about patient preferences and motivators concerning treatment adherence. We examined treatment experience across strata defined by previously identified risk correlates of non-adherence. Results: Among 60 participants, 19 (32.8%) were HIV positive, 12 (20.3%) had substance use disorder and 9 (15.0%) had not completed TB treatment. Respondents discussed the psychological distress associated with hospital-based TB care, as well as perceived unsupportive, antagonistic interactions with TB providers as major challenges to treatment adherence. An additional barrier to successful treatment completion included the financial toll of lost income during TB treatment, which was exacerbated by the additional costs of ancillary medications and transportation to ambulatory TB clinics. The high pill burden of TB treatment also undermined adherence. These challenges were endorsed among participants with and without major risk factors for non-adherence. Conclusions: Our findings highlight important barriers to TB treatment adherence in this study population and suggest specific interventions that may be beneficial in mitigating high rates of poor treatment outcomes for TB in Ukraine.